Do Russian research universities have a secret mission? a response to Forrat. Issue 4 (3rd July 2016) - Chirikov, Igor
Abstract: This paper challenges the central claim of Natalia Forrat's article that university support programs under Putin targeted the suppression of anti-regime student mobilization. Empirical evidence, both on the national-policy level and on the level of higher education institutions, suggests that the government introduced support programs in order to establish a research capacity at Russian flagship universities and to develop a more competitive national science system. The low level of students' political engagement can rather be attributed to the outdated structures of student representation, inherited from the Soviet period.